Манж, Богд хаант Монгол улсын үеийн газрын зургийн уламжлал, түүнд газрын биетийг тэмдэглэсэн нь - Ж.Нарангарав; Э.Равдан (Acta Mongolica, 2007)
The article is aimed to introduce the mapping tradition implied to the period of the Manju oppressed and Bogd Monarchy Mongolia, to observe its peculiaritics and to establish the basic toponyms marking natural objects. The research is followed by the outcomes underneath: The map of the Manju oppressed and Bogd Monarchy Monglia presents a valuable cultural and historical heritage of the country and pressing studies on it is required urgently, Previously the Mongols compiled maps in the following three ways: A whole provincial territory is observed both from the South and the North A whole provincial territory is observed from the center to all directions around in circle. An observation is made as a whole provincial territory is round tripped followed by the trips to the center. All the 74 maps being analyzed are defined in the both basic toponyms and proper names by their numbers, diversities and detailed markings and particular examples have been attached for an illustration.